Through and through suturing vs. window resection method in surgical management of seroma pinna: a comparative study - Priyadarshini, Raisa; Rautray, Subhalaxmi; Dash, Rajat Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Seroma pinna is a collection of fluid between the auricular cartilage and the perichondrium. Seromas can occur spontaneously or after surgery or trauma. Depending on the nature of swellings and the symptoms, they can be distinguished from other conditions of the pinna. Successful treatment is challenging because of high rate of recurrence. Usual treatment used to consist of aspiration of the fluid and pressure bandage. Methods include using buttons as pressure splints, excising a piece of cartilage and perichondrium to cure recurrent seromas4,placement of a continuous portable suction drain has also been advised, suturing through and though after aspiration. Methods: In the first group of patients through and through suturing was done and in the second group window resection was done. Results: The recurrence rate was 5% for the first group patients while 20% for the second group. The percentage of development of perichondritis was 5% for group A and 15% for group B. Conclusions: The method put forward in this study is a simple and effective way for its management. The avoidance of dressing is a positive factor and positive factor is that it can be done on an OPD basis.